Building Purchase Decisions in Wedding Organizer Services: The Influence of Digital Marketing Communication, Consumer Experience, and Service Quality Through Trust - Keisha Andani Devitasari; Andrian Haro; Meta Bara Berutu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purchase decisions in wedding organizer services are influenced by various factors related to marketing strategies and service quality. This study was conducted to examine the influence of Digital Marketing Communication, Consumer Experience, and Service Quality on Purchase Decision, with Trust as an intervening variable among users of wedding organizer services. The study employed a quantitative approach using a survey method through the distribution of questionnaires to 429 respondents in Jakarta who had previously used or searched for information related to wedding organizer services. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software. The results of the study indicate that Digital Marketing Communication, Consumer Experience, and Service Quality have a positive influence on Trust and Purchase Decision. In addition, Trust was found to mediate the relationship between the independent variables and purchase decisions. The findings suggest that improving the quality of digital marketing communication, consumer experience, and service quality can strengthen consumer trust and encourage higher purchase decisions in the wedding organizer industry. This study is expected to serve as a reference for business practitioners in developing more effective marketing and service strategies to enhance customer loyalty and trust.